2020
DOI: 10.1093/ser/mwaa007
|View full text |Cite
|
Sign up to set email alerts
|

New room to maneuver? National tax policy under increasing financial transparency

Abstract: Why have Organisation for Economic Co-operation and Development (OECD) governments raised taxes on dividends at the shareholder level since 2008? Previous research points to the importance of budget deficits and voter demand for compensatory fairness in the aftermath of the financial crisis. We complement this literature by showing that the effect of domestic drivers of tax increases on capital income crucially depends on the level of financial transparency in a country’s investment network. Low financial tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…Therefore, our second empirical strategy aimed at investigating the variation across countries in more detail. In Ahrens et al (2020a), and in line with the general theoretical model presented above, we argue that the variation in countries' reactions to increased transparency depends on domestic factors. Transparency alone is not sufficient to motivate governments to increase tax rates.…”
Section: Automatic Information Exchange and Domestic Tax Policysupporting
confidence: 86%
“…Therefore, our second empirical strategy aimed at investigating the variation across countries in more detail. In Ahrens et al (2020a), and in line with the general theoretical model presented above, we argue that the variation in countries' reactions to increased transparency depends on domestic factors. Transparency alone is not sufficient to motivate governments to increase tax rates.…”
Section: Automatic Information Exchange and Domestic Tax Policysupporting
confidence: 86%
“…In Denmark and Norway, the tax authorities, after detailed investigations, found that 90 to 95 percent of all HSBC account-holders had failed to report the income earned on their account (and the wealth held there in the case of Norway, where a wealth tax exists) and were thus evading taxes. 11 This result is consistent with a body of evidence suggesting that more than 90 percent of Swiss accounts were undeclared around 2007; this includes two US Senate (2008, 2014) reports finding that 85-95 percent of US-owned accounts at UBS and Credit Suisse were undeclared in 2007-2008, Roussille (2015) who estimates that more than 90 percent of the wealth held by Europeans in Switzerland was undeclared before 2010, and Johannesen and Zucman (2014) who obtain a similar estimate.…”
Section: A Hsbc Switzerland Leakmentioning
confidence: 99%
“…In addition, according to the ICI J, the biggest account at HSBC Switzerland was a US $11.9 billion account registered in the name of Venezuela's National Treasurer (who started off as a bodyguard for the late Venezuelan President Hugo Chávez). 11 This does not imply that all taxpayers with undeclared HSBC accounts have been convicted of tax evasion. In prosecuting the cases, the tax authorities face constraints.…”
Section: A Hsbc Switzerland Leakmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in part 4, our identification strategy aims at isolating the average effect of international tax cooperation on tax rates imposed on dividends. In a companion paper (Ahrens et al, 2020), we investigate the empirical interaction between fiscal transparency and the domestic factors to also explain tax rate variation across countries.…”
Section: Notesmentioning
confidence: 99%